Understanding Immune Tolerance of Cancer: Re‐Purposing Insights from Fetal Allografts and Microbes. (4th June 2018) - Barnet, Megan B.; Blinman, Prunella; Cooper, Wendy; Boyer, Michael J.; Kao, Steven; Goodnow, Christopher C.
Abstract : Cancer cells seem to exploit mechanisms that evolve as part of physiological tolerance, which is a complementary and often beneficial form of defense. The study of physiological systems of tolerance can therefore provide insights into the development of a state of host tolerance of cancer, and how to break it. Analysis of these models has the potential to improve our understanding of existing immunological therapeutic targets, and help to identify future targets and rational therapeutic combinations. The treatment of cancer with immune checkpoint inhibitors aims to reverse the progression to tolerance of cancer, and achieve an immunogenic, rather than tolerogenic, homeostasis. Broadening the efficacy and durability of checkpoint inhibitors focuses on reversing tolerance and stimulating immunogenicity in the cancer, host, and environment. Two examples of important physiological states of tolerance that may inform tolerance of cancer are microbial infection and placental reproduction. These states of tolerance result from bilateral shaping of host and non‐self, akin to immunoediting in cancer, and offer reliable models to study the immune tolerance paradigm. Abstract : Tolerance of cancer results from repurposing of physiological tolerance that has evolved under positive selective pressure. Two examples of physiological states dependent on immune tolerance are placental reproduction and the gut microbiome. Analysis of physiological tolerance can provide insight into tolerance of cancer, and how to break it.